The Correlation Between Students' Cognitive Reading Strategies and Their Reading Comprehension - Nabilah, Aurynnatasya Nurfidzah (RETAIN, 2021)
The purpose of this research was to find out the correlation students’ cognitive reading strategy and students’ reading comprehension. Another aim of this study was to find the cognitive reading strategies do the students use. The research employs a quantitative method using SORS and Reading Test Comprehension. All the samples were asked to fill the questionnaire and were taken reading test comprehension. The data gained through online questionnaire and for the reading test was done in offline at school. The sample of the study was 64 students in one of the secondary schools at Sumenep. Moreover, the result of this research revealed that the cognitive strategies that the students use were managing their reading speed when the text becomes difficult, reading the text several times to increase their comprehension to the text, back to track when they lose concentration, and the students translating the text into their native language while reading. It was found a positive correlation (p-value= 0.003, r= .371) between two variables of this research, in which the correlation coefficient was categorized as moderate.